A new species of Myrsidea (Insecta: Phthiraptera: Menoponidae) from Chile - Sychra, Oldrich; Palma, Ricardo L. (Zootaxa, 2021)
Myrsidea danielalfonsoi new species is described and illustrated from the Austral thrush (Turdus falcklandii magellanicus King, 1831) in Chile.